The Choice of the Model of the Term Structure of Interest Rates on the Basis of its Properties - ЛапшинВиктор Александрович; ТерещенкоМария Юрьевна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2018)
The article is devoted to the choice of a suitable model for construction the term structure of interest rates from the most popular ones: bootstrap, various splines, parametric Nelson-Siegel and Svensson models. The peculiarities of their use in the financial markets of the different countries are described. The problem of modeling the term structure has a long history and continues to attract increased attention of theoretical scientists and practitioners. At different times this problem was of interest to J.M. Keynes, P. Samuelson, R. Merton, F. Modigliani, M. Scholes, E. Fama, etc. Despite the serious progress in this area the question of constructing models which are adequate to real conditions is still far from the final decision and requires continuation of the work on their study. Term structure is widely used to analyze prices and bond yields, assess the fairness of market forecasts. Term structure curves are extremely important in studying the processes in economic sphere, so they need adequate models of their evaluation. In reality credits and loans interest rates are not observable at an arbitrary time moment. It remains only to model them relying on the available data on the government or corporate bonds, on other available financial instruments. All models have some advantages and disadvantages, so the specialist needs to determine the purpose of the study and select a model for it taking into account its properties. Models are considered in the chronology in which they were developed. Each subsequent model from each class was designed to eliminate the disadvantages of the previous version, but this was not always possible and the new model either reinforced weaknesses of the previous one, or produces new ones. A model choosing algorithm based on its main properties, which could become the most important for the successful solution of the problem assigned to the expert, is proposed.